Macrophage polarization in vitro and in vivo modified by contact with fragmented chitosan hydrogel. Issue 4 (1st November 2021) - von Boxberg, Ysander; Soares, Sylvia; Giraudon, Camille; David, Laurent; Viallon, Maud; Montembault, Alexandra; Nothias, Fatiha
Abstract: We have previously shown that implantation of a fragmented chitosan hydrogel suspension (chitosan‐FPHS) into a traumatic spinal cord lesion in adult rats led to significant axon regrowth and functional recovery, which was associated to a modulation of inflammation. Using an in vitro culture system, we show here that polarization of bone marrow‐derived macrophages is indeed modified by direct contact with chitosan‐FPHS. Reducing the degree of acetylation (DA) and raising the concentration of chitosan (Cp, from 1.5% to 3%), favors macrophage polarization toward anti‐inflammatory subtypes. These latter also migrate and adhere efficiently on low, but not high DA chitosan‐FPHS, both in vitro and in vivo, while inflammatory macrophages rarely invade a chitosan‐FPHS implant in vivo, no matter the DA. Our in vitro model setup should prove a valuable tool for screening diverse biomaterial formulations and combinations thereof for their inflammatory potential prior to implantation in vivo. Abstract : Impact of the chitosan‐FPHS substrate on macrophage polarization markers. (a) preparation of Chitosan‐FPHS substrate; (b) macrophage polarization marker expression in relation to chitosan concentration (Cp) and acetylation degree (DA); (c) invasion of M1 (red) and M2 (green) macrophages into a spinal cord lesion site implanted with high or low DA chitosan‐FPHS.